Climing the Mountain: Derek Parfit - Peña, Carlos (Revista de Filosofía, 2012)
This article describes the importance of Parfit ́s point of view in the public debate. The central thesis of Parfit is that three of the most outstanding points of view in moral philosophy -Kantianism, Consequencialism and, Contractualism– converge in a form of rule ́s consequentialism under Kant ́s inspiration. In support of these thesis, Parfit endorses moral realism and a externalist conception of reasons. He refuses, in this way, the underlying ideas of rational election theory.